Job Burnout: A General Literature Review - Lubbadeh, Tareq (International Review of Management and Marketing, 2020)
Job Burnout is different work-related stress syndrome portrayed by three-dimension Emotional Exhaustion, Professional inefficacy, and Cynicism. Earlier burnout research has centered on the human service professions such as nursing and teaching, where they are assumed to be the most exposed to experience burnout. However, Burnout is not confined only to social service professions but spreads to other working professions such as banking employees and managers. This paper traces the evolution of Job Burnout. It addresses the factors and the Outgrowths of job burnout and the intervention strategies to decrease or overcome it. It also presents the primary measurement of Job Burnout, the Maslach Burnout Inventory (MBI), the Burnout Measure (BM), and the Oldenburg Burnout Inventory (OLBI). Lastly, the paper closes with a brief conclusion. Keywords: Stress, Job Burnout, Emotional Exhaustion, Cynicism, Maslach Burnout Inventory. JEL Classifications: D23, J24, M10, M54 DOI: https://doi.org/10.32479/irmm.9398